Effects of Tissue Mimetic Conditions on Antibiotic Interactions Against Klebsiella pneumoniae - Morales, Yoelkys (Tufts University Tisch Library, 2025)
Thesis (Ph.D.)--Tufts University, 2023-05.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Joan Mecsas.; Committee: Aimee Shen, Linden Hu, Bree Aldridge, and Alysse Wurcel.; Keyword: Microbiology.